DILEMA ETIS KONSULTAN PAJAK DALAM TAX PLANNING - Nuraini, Dwi Endah; Sudarto, Triadi Agung; Prakoso, Dwi Hantoro (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2024)
This study aims to determine the reality of ethical dilemmas felt by tax consultants when conducting tax planning and the experience of tax consultants in overcoming this dilemma. The research method used is qualitative with an interpretive paradigm and Husserl's transcendental phenomenology approach. The informant in the study is one of the tax consultants in Blitar. The results prove that there are various forms of dilemmas felt by tax consultants, including dilemmas due to the existence of gray areas, sympathy for tax consultants for their clients and related to the sustainability of their service business. Tax consultants overcome the sense of dilemma by understanding tax regulations thoroughly, adhering to the code of ethics, and trying to increase taxpayer awareness. They achieve this by fostering understanding and providing comprehensive education on tax issues